(untitled) (Bulletin KNOB, 2000)
The ’tomb’ of count Florence V of Holland in the ‘Grote Kerk’ (St. Laurentius church) of Alkmaar has a remarkable history which can be summarized as follows. After his assassination in 1296 the body of Florence V was carried to the church of Alkmaar where it was placed in the choir, and stayed there for almost a year before it was buried in the abbey of Rijnsburg. The intestines, however, remained in the church of Alkmaar, and a donation for a memory chapel was made to commemorate the count. When in 1414 the amount of this donation was fixed again, the place where the intestines were buried was marked by an inscription on the stone below which the intestines were buried. On this stone the coffin of the count was once placed. When the church was demolished in the period 1468-1509, the stone was saved and placed on a wooden pedestal. This ’tomb’ was placed in the choir of the (present) new church. Towards the middle of the 16th century the arms of the count were painted on the wooden panels. After a restoration during the years 1998/99, the ’tomb’ has recovered its original monumental character.